Loss and Amazonian Otherness in Ecuador. - Viatori, Max (Journal of Latin American & Caribbean Anthropology, 2012)
In May 2001, the United Nations Educational, Scientific and Cultural Organization (UNESCO) declared the Zápara language part of the world's 'intangible cultural heritage.' This article examines Ecuadorian government celebrations and press coverage of the UNESCO award. It demonstrates how both employed discourses of loss and preservation that included the Zápara within the Ecuadorian nation, while simultaneously marginalizing them as cultural and political others. This case study suggests that discourses of loss have as much potential to reinforce existing hegemonies and power relations as they do to undermine them. As such, it indicates the need for anthropologists and activists to more closely scrutinize widely circulating discourses of loss and revitalization to understand how such discourses can be enabled by, work through, and reinforce colonialist narratives as much as they contest them.